(untitled) (Journal of Event, Tourism and Hospitality Studies, 2022)
This study provides contextual evidence on recreational noise exposure in a typical Nigerian urban park. It investigated perceived sonic characteristics as well as the spatial noise variations across Agodi Park and Gardens in the city of Ibadan, Oyo State, Nigeria. Integration of noise mapping and soundscape methods was used to understand the nature of noise being generated in this outdoor setting. Sound Pressure Level (SPL) was used to obtain data from nine major locations within the park. Using a non-probabilistic method of sampling, fifty respondents were selected incidentally to participate in this study. With the aid of an instrument consisting structured questionnaires and observation checklist, information on respondents’ demographic characteristics, their perceptions of the recreational noise, and desirability levels of soundscape in the park was obtained. Recreational noise data was analyzed using descriptive statistics and the Test of Difference (T-test) to investigate time-based variations in the level of noise (morning and evening periods). Although most respondents were oblivious of the noise exposure, findings show that the average sound level in the park was 77 dBA which exceeded the recommended noise limit of 60 dBA expected in recreational parks. The study recommends that soundscape characters should be considered in the design of future urban parks as they would go a long way in improving and enhancing the quality of perceived user’s comfort.